Enemy Love in Paul: Probing the Engberg-Pedersen and Thorsteinsson Thesis - Hubbard, Moyer V. (Journal for the study of Paul and his letters, 2016)
This article summarizes and critically appraises the proposals by Troels Engberg-Pedersen and Runar Thorsteinsson—in numerous publications—that Paul's love ethic was not universal in scope but was restricted to Christ-followers only. Specifically, these authors contend that, while Paul encouraged believers to be kind to everyone, he did not expect them to extend love to everyone, in particular not to their enemies. Paul's love-commands, they claim, constitute an "in-group" code of conduct, and stand in marked contrast to Stoic ethics, where love is universal in scope, extending to all humanity. This article argues that this sort of restriction of Paul's love ethic is not supported by a careful examination of the key Pauline texts, and runs against the grain of the apostle's theology, ethics, and practice. Finally, a close comparison of Paul and Musonius Rufus, one of Paul's Stoic contemporaries, on this topic will demonstrate the importance of correctly assessing the relative priorities of each ethical system for a proper evaluation of the tradition as a whole.